Perception of body-esteem among adolescents and adults : a survey - Yau, Jennifer Pillay (2011)
Low body-esteem or body dissatisfaction has been found to be correlated to depression and eating disorder and this problem is affecting individuals of different groups. This research investigates the age group difference, gender difference, and geographical location difference in body-esteem among adolescent and adults. This study is a survey research in which the participants (N = 80) were selected through purposive sampling and snowball sampling from Melaka and Manjung. The Body-Esteem Scale (BES) by Franzoi and Shields (1991) was used as the instrument to measure body-esteem in this study. The results showed that adolescents were more satisfied than adults on several items, especially adolescent females; there was a difference in body-esteem between males and females; and participants from urban and suburban population was more satisfied than the other on different items and dimensions. Specific intervention programs could be developed for different groups through this finding.